Development administration and computer databases a case analysis - Gonzalez, Joaquin L., III (1996)
This article describes the author's experience overcoming the present day dilemma of research overload due to rapid advances relating to information technology. Development administration is multidisciplinary in nature, which essentially means direct and indirect influences from a variety of fields and sub-field like public administration, sociology, political science, management, engineering, health, agriculture, and others. Consequently, this means sorting through a huge amount of literature stored in a number of expanding electronic databases. How does one muster this modern-day issue? In this article, the author elaborates on the systematic three-phase process he used to determine the extent of development administration research on the sustainability of health care projects at the village-community level.
Keywords: Database analysis and integration; Electronic data processing; Database design; Database searching -- Research evaluation